Etnobotani Tumbuhan Obat Pada Masyarakat Desa Teluk Rendah di Kecamatan Tebo Ilir Kabupaten Tebo - Adriadi, Ade; Albayudi, Albayudi; Tri Budilaksono (Jurnal Biotek, 2023)
This study aims to determine the medicinal plants used by the Teluk Low Village Community and the parts or organs of the plants used. This research was conducted in Teluk Low Ilir Village, Tebo Ilir District. This is descriptive research, with survey methods and in-depth interviews. The population in this study were the people of Teluk Bawah Ilir Village, Tebo Ilir District. The respondents were selected based on purposive sampling, where key informants and non-key informants were included. Based on the research results, 65 species from 35 families are used as medicine. The part of the plant most widely used as medicine is the leaf 52.2% (35 species), fruit 17.9% (12 species), rhizome 10.4% (7 species), bark 7.5% (5 species), stem 6.0% (4 species), sap 3.0% (2 species), and the fewest plant used as medicine parts are roots 1.5% (1 species) and tubers 1.5% (1 species).